Chemical and biological profiling of weeds and medicinal plants targeting protein kinase and phosphatases in signal transduction in cancer - Azlinah Matawali (2013)
A total of 162 methanolic extracts of plant collected from Sabah were studied and screened for novel bioactive compounds against protein kinase and phosphatases involved in signal transduction in cancer. The targeted protein screening systems were kinase (MKK1) and phosphatase (MSG5 and PP1) which using different strain of mutated yeast namely MKK1P386, MKK1P386-MSG5, PAY704-1 and PAY700-4. Screening of crude methanolic extracts showed 13 potential extracts against PP1 protein which classified as inhibitor to GLC7 (UMS71, UMS91 and UMS990); inhibitor sensitive to glc7-10 catalytic domain change (UMS80) and inhibitor insensitive to glc7-10 catalytic domain change (UMS70, UMS108, UMS901, UMS908, UMS963, UMS974, UMS975, UMS984 and UMS993). Meanwhile, about 21 and 26 crude methanolic extracts including UMS643 were found as toxic against MKK1 and MSG5 screening assay, respectively. Four extracts (UMS71, UMS91, UMS108 and UMS643) had been selected to further separate by using liquid-liquid extraction methods and subsequently re-tested against all screening assay. However, only UMS71 and UMS91 showed consistent inhibitions against PP1 screening assay. The potential extracts partitions are Chloroform (CE), Hexane (HE) and Ethyl acetate (EAE) from UMS71 and Chloroform (CE) from UMS91. They were found to be inhibitor insensitive to glc7-10 catalytic domain change with the inhibitory zones ranged between 7.33±1.15mm until 9.5±0.70mm. Thus, both UMS71 (Chromoleana odorata) and UMS91 (Mikania micrantha) had been chromatographed through Thin Layer Chromatography (TLC) and Column Chromatography. Each column fraction was screened against PP1 screening assay and the results showed 8 potential fractions from CE of UMS71. Fraction 2 (F2) was classified as inhibitor to GLC7 and exhibited strongest inhibitory zones ranged between 8.00±0.00mm until 15.0±0.0mm. As for UMS91, Fraction 2 (F2) of CE also showed activities during PP1 screening assay. This fraction was classified as inhibitor to GLC-7 with the range between 13.5±0.7mm until 14.0±1.4mm. Phytochemical test had been conducted on UMS71 dan UMS91 extracts whereas both UMS71.CE (Fraction F1-F10) and UMS91.CE (Fraction F1-F5) were scanned through UV/Vis spectroscopy. The presence of alkaloid, flavonoid, tannin, saponin and triterpenoid were observed on both samples. However, only selected fraction (UMS71.CE.F2) which possessed the most consistent and strongest antiphosphatase activities had been analysed for compounds identification by using GC-MS. The analysis revealed the presence of 10 compounds. The dominant phytocomponents in the extract fraction are hexachloro-ethane, n-nonylaldehyde, methyl-4-oxooctanoate, longiverbenone, 2-butenal,2-methyl-4-(2,6,6-trimethyl-1-cyclohexen-1-yl), neophytadiene, phytol, dihydro-neoclovene, aromadendrene and 2,6-ditert-butylquinone. Fraction UMS71.CE.F2 had also chosen to undergo the enzymatic analysis in order to determine the specificity of inhibitions against protein phosphatase type-1 (PP1). Spectrophotometric method was used to assay for the enzyme activity and both maximum enzyme velocity (Vmax) and Michealis- Menten (Km) constants were evaluated and compared for normal and inhibited reactions. The Km and Vm for substrate (DiFMUP) were 0.125mM and 125 while the Km’ and Vm’ at 300μg/μl were 0.60mM and 200.0, respectively. Other biological activities such as in-vitro cytotoxicity and antimicrobial test of UMS71 also had been reported. However, cytotoxicity test was only conducted at CE partitions level were found to exhibits cytotoxic activities against HeLa cervix adenocarcinoma (IC50 value 39.00±1.00μg/ml) cancer cell lines. Meanwhile, antibacterial test carried out for UMS71.CE.F2 showed week inhibitory activities on S. pneumonia (11.67±2.08mm), S. aureus (10.33±0.58mm), P. aeruginosa (10.67±0.58mm), E. coli (8.00±0.00mm) and S. typhii (8.00±0.00mm) when compared to ampicillin as control positive.